A crossover study comparing gabapentin and fluoxetine for the treatment of vasomotor symptoms among postmenopausal women. Issue 1 (October 2015) - Rahmanian, Mojgan; Mohseni, Arash; Ghorbani, Raheb
Abstract Objective To compare the effectiveness of fluoxetine and gabapentin for treatment of vasomotor symptoms (VMS) after the menopause. Methods Between March 2011 and March 2012, a randomized crossover study was performed at a center in Semnan, Iran, among postmenopausal women aged 45–57 years with hot flashes (≥ 2 per day for previous 4 months) for which they had received no previous treatment. Participants were divided into two groups with consecutive numbers assigned in order of recruitment. In the first treatment round (4 weeks), group A received 20 mg/day fluoxetine and group B received 300 mg/day gabapentin. After a 2-week washout period, group A received gabapentin and group B received fluoxetine in a second round (4 weeks). Information about VMS was obtained with the Greene Climacteric Scale questionnaire. Participants and all investigators except one were masked to group assignment. Results Data for 79 participants (39 in group A, 40 in group B) were analyzed. In both treatment rounds, gabapentin caused greater reductions in the severity of hot flashes than did fluoxetine (P < 0.001 for both). After the first round of treatment, those who had received gabapentin reported greater reductions in the severity of night sweats (P < 0.001). Conclusion Gabapentin at a dose of 300 mg/day is more effective for treatment of VMS among postmenopausal women than is 20 mg/day fluoxetine. Iranian Registry of Clinical Trials: IRCT2014092711019N3 .